Enhancing urban resilience in face of climate change: a methodological approach - Galderisi, Adriana; Ferrara, Floriana Federica (TeMA - Journal of Land Use, Mobility and Environment, 2012)
Climate change can be considered as one of the main environmental topic of the 21st century (IPCC, 2011). It poses a serious challenge for cities all over the world (EEA, 2012): cities show, on the one hand a high level of vulnerability in face of climate change, on the other hand, they are responsible for 60% to 80% of global energy consumption and greenhouse gas (GHG) emissions, which represent the main causes of change in climate conditions. In 2011, the 73% of European population was living in urban areas and the level of urbanization is expected to be at 82% by 2050 (UN, 2012). Due to the evidence that in Europe the 69% of all GHG emissions are currently generated by cities, larger and larger is the attention devoted, by scientific literature and policy makers, to outline strategies for urban adaptation to climate change, both at European and local scale. Governments and scholars currently highlight the need for strengthening urban resilience in face of climate change and related consequences. By this perspective, some actions are already running, even though a clear identification of the features which make a city resilient in face of climate change is still missing. To fill this gap, this contribution is mainly addressed to: - provide, by integrating different disciplinary perspectives, a conceptual model of the set of adaptive capacities and properties that characterize a resilient system; - verify, starting from a snapshot of current strategies and actions for urban adaptation currently implemented at European level, the consistency between those strategies and the identified set of resilience capacities and properties.